2016
DOI: 10.1111/hsc.12313
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about care home managers? Findings of a scoping review

Abstract: This article reports selected findings from a scoping review of the literature about care home managers in England. The review was undertaken between December 2013 and April 2014, with searches conducted in December 2013, and completed in July 2014. Its aim was to identify the characteristics of care home managers, descriptions of their leadership and managerial roles, their experience, skills and support, and the managers' perceptions of their work and status and to identify knowledge gaps. The databases sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Registered managers roles are complex, often experienced as ambiguous and include significant administrative demands (e.g., Orellana et al, 2017;Beadle-Brown et al, 2006;Bradshaw et al, 2018;Deveau & McGill, 2016b;Clement & Bigby 2012). Depending upon organisational expectations of RM, which may prioritise administrative work (Mansell & Elliott, 2001) this ambiguity and administrative load is likely to clash with providing PL.…”
Section: Discussionmentioning
confidence: 99%
“…Registered managers roles are complex, often experienced as ambiguous and include significant administrative demands (e.g., Orellana et al, 2017;Beadle-Brown et al, 2006;Bradshaw et al, 2018;Deveau & McGill, 2016b;Clement & Bigby 2012). Depending upon organisational expectations of RM, which may prioritise administrative work (Mansell & Elliott, 2001) this ambiguity and administrative load is likely to clash with providing PL.…”
Section: Discussionmentioning
confidence: 99%
“…As Scales et al (2017) were observed in relation to handover timings, participants, locations and content -and these all have implications for resident safety. It might be expected this would be the case given the variability of residents' dependency levels and the aim of offering personalised care and the key role of a manager in shaping care home culture (Orellana et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the few papers identified, unlike Burra et al 61 and Ennis et al 62 we did not adopt a critical appraisal approach to rating the quality of studies, thereby following procedures generally categorised as scoping reviews. 63 One key reason for this is that such an approach risks overlooking studies with small sample sizes and, thus, might exclude individual case study or whole-hostel research if the numbers of older residents were not sizeable. Ennis et al 62 considered a sample size of over 100 to be 'good', but, as discussed below, we found few studies reporting such numbers.…”
Section: Process Of the Reviewmentioning
confidence: 99%